Hubungan antara Pola Asuh Orang Tua Demokratis terhadap Efektifitas Belajar Siswa - Abel, Rizky Mayesita Aryance; Upa, Muhammad Dae Pua (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
This study aims to describe the parenting style (democratic parents), the effectiveness of learning patterns, and the relationship between parenting style (democratic parents) and the effectiveness of learning in students at middle school. This study uses a quantitative approach to the type of descriptive correlational research. The study included 83 students and used purposive sampling. The data was collected using an instrument with a Likert scale model. The analysis technique used descriptive analysis and correlational analysis with SPSS Version 16. The findings in this study show that students at SMP Negeri 16 Kupang City have a democratic parenting style in the high category (96%) and the learning effectiveness of students (90%). Product moment correlation analysis shows that democratic parenting is related to learning effectiveness with a significant value of 0.012 (p < 0.05) and the Pearson Correlation value is 0.795 which indicates that the relationship between the two variables is strong. The positive direction where n = 83 and degrees of freedom (dk) is 80 with a significance level of 0.05, so it is known that the r table is 0.2159 (rtabel: 0.795 > rhitung: 0.2159). Here it can be interpreted that democratic parenting style has a strong positive relationship to the effectiveness of learning in students of SMP Negeri 16 Kota Kupang.